Paclitaxel-Loaded Nanosponges Inhibit Growth and Angiogenesis in Melanoma Cell Models - Clemente, Nausicaa; Argenziano, Monica; Gigliotti, Casimiro Luca; Ferrara, Benedetta; Boggio, Elena; Chiocchetti, Annalisa; Caldera, Fabrizio; Trotta, Francesco; Benetti, Elisa; Annaratone, Laura; Ribero, Simone; Pizzimenti, Stefania; et al. (Frontiers in Pharmacology, 2019)
This study investigated the effects of free paclitaxel (PTX) and PTX-loaded in pyromellitic nanosponges (PTX-PNS) in reducing in vitro and in vivo melanoma cell growth and invasivity, and in inhibiting angiogenesis. To test the response of cells to the two PTX formulations, the cell viability was evaluated by MTT assay in seven continuous cell lines, in a primary melanoma cells, both in 2D and 3D cultures, and in human umbilical vein endothelial cells (HUVEC) after exposure to different concentrations of PTX or PTX-PNS. Cell motility was assessed by a scratch assay or Boyden chamber assay, evaluating cell migration in presence or absence of diverse concentrations of PTX or PTX-PNS. The effect of PTX and PTX-PNS on angiogenesis was evaluated as endothelial tube formation assay, a test able to estimate the formation of three-dimensional vessels in vitro. To assess the anticancer effect of PTX and PTX-PNS in in vivo experiments, the two drug formulations were tested in a melanoma mouse model obtained by B16-BL6 cells implantation in C57/BL6 mice. Results obtained were as follows: 1) MTT analysis revealed that cell proliferation was more affected by PTX-PNS than by PTX in all tested cell lines, in both 2D and 3D cultures; 2) the analysis of the cell migration showed that PTX-PNS acted at very lower concentrations than PTX; 3) tube formation assay showed that PTX-PNS were more effective in inhibiting tube formation than free PTX; 4) in vivo experiments demonstrated that tumor weights, volumes and growth were significantly reduced by PTX-PNS treatment with respect to PTX; the angiogenesis and the cell proliferation, detected in the tumor samples with CD31 and Ki-67 antibodies respectively, indicated that in the PTX-PNS-treated tumors the tube formation was inhibited and a lor amount of proliferating cells was present. Taken together our data demonstrated that our new PTX nanoformulation can respond to some important issues related to PTX treatment, lowering the anti-tumor effective doses and increasing the effectiveness in inhibiting melanoma growth in vivo.